PENGARUH GENDER DEWAN KOMISARIS, GENDER DEWAN DIREKSI, DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA PERUSAHAAN - Famera Hanani; Y Anni Aryani (Akademi Akuntansi YKPN Yogyakarta, 2011)
The objective of this study is to examine the influence of corporate governance mechanisms, which are board of director’s gender, director’s gender, and managerial ownership on firm’s performance. This study also examines firm’s size, leverage, and firm’s age, as control variables, on firm’s performance. This study uses 111 listed companies’ annual reports on Indonesia Stock Exchange (BEI) year 2008. Sample in this study is selected using purposive sampling method. While multiple regression analysis is used to test the three hypotheses developed in this research. The result of this study shows that (1) board of director’s gender has negative influence on firm’s performance, (2) director’s gender does not influence the firm’s performance, and (3) managerial ownership also does not influence the firm’s performance.Keywords: board of director’s gender, director’s gender, managerial ownership, firm’s performance, Tobin’s Q